T cell subsets in cervical cancer tumor microenvironment: advances and therapeutic opportunities - Guo, Weilin; Dai, Lan; Qiu, Lihua (Frontiers in Immunology, 2025)
Cervical cancer is the third most common malignancy among Chinese women in both incidence and mortality. Its progression is closely linked to complex interactions among immune cells within the tumor microenvironment (TME). As key components of the immune landscape, different T cell subsets play diverse and dynamic roles in shaping tumor immunity. This review provides a comprehensive overview of the roles of various T cell subsets in the TME of cervical cancer, with a focus on their distribution, functional heterogeneity, dynamic balance, and variations across different pathological subtypes and disease stages. We also highlight the intricate crosstalk between T cells and other immune cells in the TME and discuss recent advances in T cell-related immunotherapies for cervical cancer, including immune checkpoint inhibitors and HPV-targeted vaccines. By elucidating the roles of distinct T cell subsets and relevant immunotherapeutic approaches within the TME, this review provides insights into potential therapeutic targets and approaches for improving cervical cancer treatment and patient outcome.